ANALISIS ASPEK VICTIM ATTRIBUTION PADA REINFORCER BYSTANDER DALAM CYBER BULLYING KALANGAN GENERASI Z - Devica, Gracella Shenie; Putri, Jesselena Arinda; Kunardi, Maria Jessica; Tanujaya, Regyta Starlameivia; W, M. M. Tri Warmiyati Dwi (Atma Jaya Catholic University of Indonesia, 2024)
In cyber bullying cases, there are three categories of parties involved, such as perpetrators, victims, and bystanders. This study analyzed the overview of victim attribution in reinforcer bystanders involved in cyberbullying incidents among Generation Z. This study uses qualitative methods with a semi-structured interview. The study shows that individuals’ perspectives on tolerating cyberbullying events vary. The four participants who were bystanders in the cyberbullying showed both victim attribution aspects, which are dehumanization and attribution of blame. Participants tend to blame the victim when they think that the victim is at fault. Therefore, in certain cases of cyberbullying, participants tend to normalize or consider it appropriate for cyberbullying to occur.